The influence of problem-based learning model on students’ learning outcomes - Abdurahman, Ayi; Asfahani, Asfahani; Sudarwati, Ninik; Warwer, Fredrik; Asrijal, Andi (SAINTIS Publishing, 2023)
This study is motivated by the importance of using various learning models in learning at school. In learning students tend to be passive and only act as recipients of information from the teacher. In addition, the learning model used by teachers is still conventional or teacher-centered. The purpose of this study was to explain the effect of the Problem-Based Learning model on students' learning outcomes. The method used in this study is a quantitative experiment. While the population of this study were MA class students. Mambaul Ulum Islamic Boarding School Malang, with a sampling technique that is saturated sampling. The data collection technique used is documentation of student scores and questionnaires. Based on the results of testing the hypothesis that the Problem Based Learning Model influences Aqidah Akhlaq Learning Outcomes at Madrasah Aliyah Miftahul Ulum, according to the records of the Aqidah Akhlaq subject teacher scores show an average value of 77.4 which is included in the very good category. So, it can be concluded that student learning outcomes in the Aqidah Akhlaq subject at Mambaul Ulum Islamic Boarding School Malang are influenced by one of the learning models, namely Problem Based Learning.